Regional Development Environment, Local Government’s Character Behavior, and Sustainability: Empirical Evidence from China - Zhou, Rong; Wang, Jian; Yu, Dengke (Problemy Ekorozwoju, 2023)
After the rapid economic growth through reform and opening-up over 40 years, Chinese governments are seeking transformation for high-quality and sustainable development currently. Regional economic development is related to internal and external environments as well as local government’s character behaviors. Employing Neuro Linguistic Programming (NLP) and Consciousness-Context-Behavior (CCB) theory, we construct a theoretical framework to measure the relationships between regional development environment (RDE), local government’s character behavior (LGCB), and regional sustainable capability (RSC). We collect the data of 30 provinces in mainland China from 2001 to 2020 to conduct hypothesis testing and empirical analysis. The results show that both RDE and LGCB are associated with RSC, and LGCB significantly mediates the relationship between RDE and RSC. However, the effects of different RDE elements on RSC are heterogeneous. Our study enriches regional sustainable development theory. It arouses us to better understand LGCB and attach importance to the roles of RDE and LGCB in regional sustainability. The enlightenment is important to global developing countries.